Research on Development and Application of NG-PON2 - Ming Jiang; Chengbin Shen; Jialiang Jin (Dianxin kexue)
The general requirements for NG-PON2 technology and its overlay configuration based on TWDM PON ＆amp;point-to-point WDM were introduced briefly.The architecture of NG-PON2 system and mixture of multiple technologies over reused ODN were analyzed.And then the main technical features and key technologies in NG-PON2 system were investigated.Finally,the progress of standardization and eco-system were introduced.